Study of Dermatophytes and incidence of different clinical types of Tinea in skin OPD - S, Singh; A, Kumar; A, Agrawal; R, Singh (Eastern Journal of Medical Sciences, 2016)
Dermatophytes (keratinophilic fungi) are very common cutaneous mycoses. Materials and methods: The study was done to determine the proportion and distribution of dermatophytes among patients coming to a tertiary care hospital with clinically suspected ringworm lesions, taking into account different parameters like age, sex, occupation of the patient, socio-economic status and nature of the skin condition. One hundred clinically diagnosed cases of dermatophytosis were studied. Results: Based on direct microscopy and culture, it was concluded that the most common clinical type was Tinea corporis and the most common dermatophyte was Trichophyton rubrum. Infections were more common in manual laboureres and males. Conclusion: They are very common infections and proper samples collection and processing are keys to diagnosis.